Wound data record to produce nursing-sensitive care indicators - Teixeira, Paula Alexandra; Silva, Luciana Pelluzi (Revista Fontes Documentais, 2024)
Introdução: Health data contain information relevant to clinical decision-making. The way they are collected and stored makes it difficult to use them for analysis and quality care assessment. Wound care is no exception and sometimes they may not even contain all the necessary clinical information, with missing or discrepant values occurring or having large datasets with detailed wound information, insights or outcomes that cannot be used for wound care assessment (MADU, 2012). Nurses spend 13 to 28% of their total shift time recording the care provided and documentation is poor explored or used. Data quality is critical to patient safety, high-quality care, quality assurance, and demonstrating nursing’s contribution to patient. No universal standardized terminology has been established and there are several nursing-specific (NANDA, ICNP) and multidisciplinary standardized termi- nologies approved for clinical practice.